The Pear Aroma in the Austrian Pinot Blanc Wine Variety: Evaluation by Means of Sensorial-Analytical-Typograms with regard to Vintage, Wine Styles, and Origin of Wines - Christian Philipp; Phillip Eder; Walter Brandes; Elsa Patzl-Fischerleitner; Reinhard Eder (Journal of Food Quality)
The perceived pear aroma in wines was associated with various short- and medium-chain ester compounds. A consumer study confirmed this assumption. In total, eight ester compounds from a series of 100 aromatic substances were associated with the pear aroma. In this study, a valid stable isotope dilution assay headspace solid-phase microextraction gas chromatography mass spectroscopy (SIDA-HS-SPME-GC-MS) method was developed for the analysis of these compounds, and 102 Austrian Pinot blanc wines of vintages 2013–2016 were analysed. They were assessed with regard to vintage and origin influences as well as wine styles. However, an attempt was made to capture the synergies of these compounds for the pear aroma. With the detection of ethyl (E,Z)-2,4-decadienoate and methyl (E)-geranoate, two volatile compounds were measured which had not previously been detected in Austrian wines. The eight analysed esters were perceived very differently. Therefore, specific odour activity values for the various sensations could be calculated with a mathematical combination of the analyses and the results of the sensory studies. A vintage influence on the sensorial descriptor “overripe pear” and a relationship between wine style and total pear aroma were determined.